2013
DOI: 10.3389/fnsys.2013.00071
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory changes in cortical resource allocation in adults with hearing loss

Abstract: Hearing loss has been linked to many types of cognitive decline in adults, including an association between hearing loss severity and dementia. However, it remains unclear whether cortical re-organization associated with hearing loss occurs in early stages of hearing decline and in early stages of auditory processing. In this study, we examined compensatory plasticity in adults with mild-moderate hearing loss using obligatory, passively-elicited, cortical auditory evoked potentials (CAEP). High-density EEG eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
161
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(188 citation statements)
references
References 77 publications
23
161
0
4
Order By: Relevance
“…Campbell and Sharma (2013), in an electroencephalography (EEG) study, supported this notion by showing that hearing loss is associated with the reallocation of cortical resources, from temporal areas to frontal cognitive areas, which presumably aid the processing and reconstruction of auditory stimuli, even in passive listening conditions.…”
Section: The Role Of Explicit Cognitive Functioning In the Recognitiomentioning
confidence: 86%
See 1 more Smart Citation
“…Campbell and Sharma (2013), in an electroencephalography (EEG) study, supported this notion by showing that hearing loss is associated with the reallocation of cortical resources, from temporal areas to frontal cognitive areas, which presumably aid the processing and reconstruction of auditory stimuli, even in passive listening conditions.…”
Section: The Role Of Explicit Cognitive Functioning In the Recognitiomentioning
confidence: 86%
“…These findings can be explained by two mechanisms: first, poor sensory coding of consonants and words by EHA users places higher processing demands on perception (ELU model, Rönnberg et al, 2013); second, changes in the structural and functional auditory system of EHA users make the processing of consonants and words cognitively demanding, even when hearing aids are used (cf. Campbell & Sharma, 2013). …”
Section: ! ! 36!mentioning
confidence: 99%
“…The impact is not only on the linguistic level, but is reflected in a brain reorganization, transferring auditory cortical areas for visual processing even in subjects with mild-moderate hearing impairment acquired in adulthood (24,25) . Therefore, the lack of correlation between the degree of hearing loss and receptive vocabulary, in this study, can be attributed to the fact that all subjects were analyzed, somehow, and constrained by disability.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the variable "degree of hearing loss" represented one of the limits of research, because there were only two representatives with mild hearing loss, so that, for further statistical analysis would be necessary to develop a more extensive study with increasing the sample. Considering the effect of hearing loss on brain organization, described above (24,25) , and the factors related to participation restriction and reduction of language experiences, would be supposed that subjects with hearing loss no longer had a greater reduction of receptive vocabulary. However, no correlation was found between duration of hearing loss and receptive vocabulary.…”
Section: Discussionmentioning
confidence: 99%
“…During the performance of auditory tasks, hearing loss was associated with lower activity in brain regions involved in speech processing (brain-stem, thalamus, and superior temporal gyri; Peelle et al, 2011), while others have observed an increased activity in the pre-frontal cortex, associated with WM processing (Campbell and Sharma, 2013). With hearing loss relating to structural changes in the cochlea and the brain, it is assumed that the neural signatures of speech processing are likewise affected.…”
Section: Neural Speech Processingmentioning
confidence: 99%